Zoneamento ambiental como instrumento de planejamento e gestão do perímetro urbano e de áreas verdes do município de Campina do Monte Alegre – SP - Gallassi, Camila (Universidade Federal de São Carlos, 2023)
An instrument of the National Environmental Policy and City Statute, Environmental Zoning is an important tool in organizing the territory, responsible for dividing it according to areas where certain activities are authorized or not, in view of their social, economic and environmental characteristics. Several problems of urban feature can arise without this planning, including the occupation of irregular areas, pollution and the decrease in environmental quality, with consequences for the health and well-being of population, the reduction of green areas, which often end up being disregarded by government and the population, among others. Considering planning and management issues concerning about municipal Urban Growth Boundary and green areas that include it, this study sought to provide mens for this instrument to be adopted by the public authorities in the municipality of Campina do Monte Alegre – SP, located in countryside of state of São Paulo and belonging to one of the regions with the lowest human development index in this State, but with potential for growth due to the city’s proximity to a campus of Federal University of São Carlos. For this, maps were generated from drone imagens, topographic maps and shapefiles, indicating the built-up areas (totaling 295,040 m² of built area inside Urban Growth Boundary), the population density related to these areas (0,017 inhab/m², equivalent to one inhabitant per 57.3 m² of built area) and occupancy rate of the Urban Growth Boundary (5% from the total urban area and 17,88% of total High Density Building Areas), maps characterizing physical aspects, maps indicating the areas of environmental restriction, the urban voids, the amount of green areas in the municipality and possible regions for urban and green areas expansion.
Environmental zoning as a planning and management instrument of the urban perimeter and green areas in Campina do Monte Alegre – SP
Keywords: Zoneamento ambiental; Planejamento e gestão urbana; Áreas verdes urbanas; Environmental zoning; Urban planning and management; Urban green areas; ENGENHARIAS